ANALISIS EFISIENSI, PERTUMBUHAN DAN KESERASIAN BELANJA DAERAH PADA BADAN PENDAPATAN DAERAH KABUPATEN BENGKALIS - Ema; Fitriyadi Trisuswanto (STAI Miftahul Ulum Tanjungpinang, 2023)
The purpose of this risearch was to determine the financial performance of the government in the management of local revenue (BAPENDA) in Bengkalis Regency. Performance analysis has been carried out more specifically to government expenditure based on Audited Budget Realization Report (LRA) of the Period 2018-2020. This risearch used expenditure efficiency analysis, expenditure growth analysis and expenditure compatibility analysis. This study used descriptive qualitative methode by collecting and processing data. Based on the result of the study by using the expenditure eficiency analysis show that the amount of spending was efficient for periode 2018- 2020. And then the expenditure growth analysis, the amount of spending has increased 2018 to 2019. Different result for the expenditure growth analysis period 2019-2020, the amount of spending rate has decreased And then the result of expenditure compatibility analysis, the amount of spending was normal as usual.